‘Squeezing Out’ the Nile Delta’s drainage water to irrigate Egypt’s desert land - Tawfik, Mohamed; Hoogesteger, J.; Moussa, M.; Hellegers, P. (MDPI, 2024)
Egypt’s quota of Nile River water has been constant since the 1950s, despite the continual agricultural land expansion. To facilitate land reclamation, Egypt has reallocated Nile water from downstream users, mostly smallholders in the ‘old lands’ of the Delta. As water demands have grown, more attention has gone to the reuse of waste/drainage water as a reliable source for irrigated agriculture in the “old lands”. Recently, new mega plants for drainage water treatment have been built to promote reclamation of ‘new lands’ in desert-front governorates located outside the Nile Delta. Through these plants and the related water conveyance infrastructure, drainage water from the ‘old lands’ is now being collected, treated, and reallocated to these newly reclaimed areas. This article scrutinizes this transformation of access to drainage water, examining who benefits and what implications it holds for smallholder farmers in the old lands. The analysis suggests that waste/drainage water reclamation schemes do not tap into unused water but actually risk depriving smallholders in the Nile Delta of water access. It argues that more attention should be given to existing informal reuse arrangements and that smallholders’ access to water is guaranteed in light of new drainage water reuse projects.